Inhibition Effect of Ca2+ Ions on Sucrose Hydrolysis Using Invertase - Hargono Hargono; Bakti Jos; Abdullah Abdullah; Teguh Riyanto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
Fermentable sugar for bioethanol production can be produced from molasses due to its high sucrose content but Ca2+ ions found in the molasses may affect the hydrolysis. Therefore, this paper was focused to study the effect of Ca2+ ions as CaO on sucrose hydrolysis using invertase and to obtain the kinetic parameters. The kinetic parameters (KM and Vmax) were obtained using a Lineweaver-Burk plot. The value of KM and Vmax parameters were 36.181 g/L and 21.322 g/L.h, respectively. The Ca2+ ions act as competitive inhibitor in sucrose hydrolysis using invertase. Therefore, the inhibition mechanism was followed the competitive inhibition mechanism. The value of inhibition constant was 0.833 g/g. These parameters were obtained from the non-substrate inhibition process because this study used the low substrate concentrations which means the fermentable sugar production was low. Hence, there were still more challenges to studying the simultaneous effect of substrate and Ca2+ on sucrose hydrolysis to produce high fermentable sugar.